A systematic in-vitro and in-silico approaches on evaluation of commercially available Metformin Hcl tablets. (18th March 2011) - Seenivasagam, R.; Hemavathi, K.
The main objectives of the investigational study are in-vitro and in-vivo evaluation of Metformin Hcl tablets on Non-Insulin Dependent Diabetic Mellitus (NIDDM). Various tablet parameters were evaluated through in-vitro tests on marketed brands of Metformin Hcl tablets. The results obtained earlier are correlated with variation in dissolution profiles the dissolution profiles of the marketed brands with regard to any possible bio-equivalence are analysed. In-silico studies are important to locate molecular targets for NIDDM. Through homology modelling and active-site prediction, the suitable protein and receptor for Metformin Hcl were identified.